Indo- Israeli Initiative for the Development of Rural Sector in India. - Sherman, Martin (2009)
The development of rural India will, in all likelihood, be one of largest and most significant undertakings this century. Given the democratic nature of governance in the country and the decisive influence of the rural voter on electoral outcomes, such development is a political imperative that entails vast economic opportunity – for both the domestic business sector and for foreign partners who have the foresight to participate, in and contribute to, this mammoth enterprise. Long-term, sustainable development cannot be limited to enhancement of production performance per se. It requires a holistic approach, addressing the entire complex of rural activity – from pre–arvest preparation to post-harvest processing; from agro-logistics to the creation of non-farming employment and income. Israel, as an acknowledged world leader in many of the relevant competencies required for a comprehensive upgrading of rural India, is uniquely equipped with both the innovative expertise and the accumulated experience to be a major partner in such an initiative. A five stage “roadmap” for implementation of an Indo-Israeli collaborative venture for the advancement of rural India is set out